2020
DOI: 10.3390/ijms21031058
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Insulin-Like Growth Factor 1 Receptor Delays M-Phase Progression and Synergizes with Aurora B Inhibition to Suppress Cell Proliferation

Abstract: The insulin-like growth factor 1 receptor (IGF1R) is a receptor-type tyrosine kinase that transduces signals related to cell proliferation, differentiation, and survival. IGF1R expression is often misregulated in tumor cells, but the relevance of this for cancer progression remains unclear. Here, we examined the impact of IGF1R inhibition on cell division. We found that siRNA-mediated knockdown of IGF1R from HeLa S3 cells leads to M-phase delays. Although IGF1R depletion causes partial exclusion of FoxM1 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Furthermore, the cleaved caspase-3–positive cells were observed in the cells treated by inhibitors and the number of cleaved caspase-3–positive cells were significantly increased upon the combination treatment ( Figure 1 a,b). Considering that the number of cells after 72 h of combination treatment was less than that of seeded cells (Figure 7B in [ 16 ]), these results suggest an involvement of cell death in suppression of cell proliferation. It is worthy to note that the cleaved caspase-3–positive cells generated by the combination treatment appear to be larger than those obtained by either OSI-906 or ZM447439 treatment ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the cleaved caspase-3–positive cells were observed in the cells treated by inhibitors and the number of cleaved caspase-3–positive cells were significantly increased upon the combination treatment ( Figure 1 a,b). Considering that the number of cells after 72 h of combination treatment was less than that of seeded cells (Figure 7B in [ 16 ]), these results suggest an involvement of cell death in suppression of cell proliferation. It is worthy to note that the cleaved caspase-3–positive cells generated by the combination treatment appear to be larger than those obtained by either OSI-906 or ZM447439 treatment ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective analysis of patients with cervical cancer showed that IGF1/IGF1R signaling is involved in tumor formation and clinical outcome [ 8 ]. We previously reported that although 3 µM OSI-906 suppressed 48% of cell proliferation, combination with 1 µM ZM447439, which caused almost no suppressive effect, suppressed 74% of cell proliferation of cervical cancer HeLa S3 cells [ 16 ]. However, the precise mechanism behind this effect is yet to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations